Migrants’ Settlement in Malaysia: Nurturing Sustainable Urban Development through Housing Rights - Sohaimi, Nor Suzylah; Mohd Arshad, Mohd Ramlan; Ajis, Mohd Na’em; Jasni, Mohd Alif (Faculty of Geography, Universitas Gadjah Mada, 2025)
Aspects of adequate housing encompass affordability, habitability, accessibility, location, cultural appropriateness, and accessibility of resources such as services, materials, utilities, and infrastructure. Migrant settlement and housing issues in Malaysia have been a persistent problem for many years. Numerous migrants are compelled to live in cramped and unsafe circumstances due to various factors, including a lack of living space, inadequate government policies, and social stigma. Surprisingly, the housing aspect of integrating regular migrants has received little focus than other integration efforts. Both locals and migrants are impacted by this apathy and vulnerability. Key guiding principles that support the right to a reasonable standard of living, which includes sufficient housing, are found in the 17 Sustainable Development Goals (SDGs), particularly SDG 11: Sustainable Cities and Communities. Therefore, this article aims to explore the issues and challenges of migrants’ settlement in Malaysia’s urban area and propose suggestions to reduce the settlement issue among migrants. Correspondingly, this study employed a qualitative methodology that combined a thorough literature review with semi-structured interviews and subsequent thematic analysis. The findings show that uncomfortable living conditions for locals and overcrowding are major issues in migrant settlements. Five strategies are suggested to address these issues: creating housing cooperatives and modular dwellings; transforming emergency housing into long-term solutions; and reusing accessible derelict buildings.Received:2024-02-13 Revised:2024-02-23 Accepted: 2025-04-14 Published: 2025-04-27